2015
DOI: 10.1002/etc.2796
|View full text |Cite
|
Sign up to set email alerts
|

Hg‐contaminated terrestrial spiders pose a potential risk to songbirds at Caddo Lake (Texas/Louisiana, USA)

Abstract: Methylmercury (MeHg) is an environmental contaminant that can have adverse effects on wildlife. Because MeHg is produced by bacteria in aquatic ecosystems, studies of MeHg contamination of food webs historically have focused on aquatic organisms. However, recent studies have shown that terrestrial organisms such as songbirds can be contaminated with MeHg by feeding on MeHg-contaminated spiders. In the present study, the authors examined the risk that MeHg-contaminated terrestrial long-jawed orb weaver spiders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 24 publications
1
54
2
1
Order By: Relevance
“…near Caddo Lake (Texas/Louisiana, USA) and its associated wetlands exceeded the minimum tissue MeHg concentrations (19.4–256 ng/g) that would cause physiological impairment in arachnivorous birds (USEPA ), and the mean MeHg concentration found in Tetragnatha spiders in this study was 3.9 times higher than the highest MeHg concentration reported by Gann et al. (). Moreover, MeHg concentrations in spiders in our study sites were also higher than in fish collected from the same streams (H. J. Broadley et al., unpublished manuscript ), emphasizing the importance of MeHg bioaccumulation across aquatic–terrestrial boundaries in non‐piscivorous terrestrial consumers.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…near Caddo Lake (Texas/Louisiana, USA) and its associated wetlands exceeded the minimum tissue MeHg concentrations (19.4–256 ng/g) that would cause physiological impairment in arachnivorous birds (USEPA ), and the mean MeHg concentration found in Tetragnatha spiders in this study was 3.9 times higher than the highest MeHg concentration reported by Gann et al. (). Moreover, MeHg concentrations in spiders in our study sites were also higher than in fish collected from the same streams (H. J. Broadley et al., unpublished manuscript ), emphasizing the importance of MeHg bioaccumulation across aquatic–terrestrial boundaries in non‐piscivorous terrestrial consumers.…”
Section: Discussioncontrasting
confidence: 57%
“…Gann et al. () found that Tetragnatha sp. near Caddo Lake (Texas/Louisiana, USA) and its associated wetlands exceeded the minimum tissue MeHg concentrations (19.4–256 ng/g) that would cause physiological impairment in arachnivorous birds (USEPA ), and the mean MeHg concentration found in Tetragnatha spiders in this study was 3.9 times higher than the highest MeHg concentration reported by Gann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Odonate‐based avian wildlife values were calculated to assess the exposure risk for nestling red‐winged blackbirds at the study site using methods modified from the US Environmental Protection Agency , Lazorchak et al , Walters et al , and Gann et al (Supplemental Data). Odonate‐based avian wildlife values reflect the minimum MeHg concentrations in odonates, consumed by birds in normal proportions of the total diet, required to create physiologically significant doses .…”
Section: Methodsmentioning
confidence: 99%
“…Shoreline spiders have been proposed as biosentinels that could be used to monitor biomagnifying contaminants in aquatic ecosystems (Walters et al 2008(Walters et al , 2009Otter et al 2013;Tweedy et al 2013) and provide insight into the risk posed by contaminants to birds that feed on spiders (Walters et al 2009;Gann et al 2015). Most studies have focused on long-jawed orb weavers that have potential as biosentinels because they have a wide geographic distribution, occur at high densities, and specialize in the consumption of emergent aquatic insects (Walters et al 2008).…”
Section: Resultsmentioning
confidence: 99%